Integrated management for the Chinchipe transboundary basin in northern Peru - Dilas-Jiménez , Josué Otoniel (2021)
The integrated management of the basin must be analyzed from a complex point of view and from the different perspectives that address it. The implementation of integrated watershed management actions and plans is not easy, given the high variability of the territory in the Peruvian case, especially when it comes to transboundary watersheds. The Chinchipe basin, Peru-Ecuador transboundary basin, is part of the Amazonian slope, it is located in a strategic and productive area of ​​northern Peru, mainly in the territory of the Cajamarca region, the agricultural activity with coffee cultivation predominates in the middle basin and rice crops, cocoa, other crops in the lower basin. Among its main weaknesses for integrated management is the non-conformation of the Basin Water Resources Council as a basic institutional actor of the system according to Peruvian Law, the limited empowerment of the Chinchipe-Chamaya Local Water Authority, the scarce integration of the actors of the basin, among others. However, it has been analyzed that this basin has a high potential to contribute to the development of the territory, therefore, this document develops a proposal for integrated management of the Chinchipe basin.